Managing technology entrepreneurship and innovation - Trott, Paul; Hartmann, Dap; Duin, Patrick, van der; Scholten, Victor; Ortt, Roland (New York : Routledge, 2016)
'As entrepreneurship education expands, increasing numbers of educational institutions are requiring students in science and engineering to be taught about entrepreneurship, management and innovation. Existing textbooks in these areas are focused on business students and are often inappropriate for science and engineering students.This is the first comprehensive, rigorous and yet accessible textbook for non-business based entrepreneurship courses. Authored by a team with experience of science and industry, the book synthesises the major research in the field, providing students with the knowledge needed to enhance case discussion and analysis. In particular it links the entrepreneur with all the innovation activities necessary to turn technology into a business.This accessible text will be useful for all non-business students who need to understand entrepreneurship, management and innovation. It will also prove a useful introduction to all Masters-level students taking these subjects in business schools.'--
'This is the first comprehensive, rigorous and accessible textbook for non-business based entrepreneurship courses, focussed on students with a background in science and technology. Written by an author team with a wealth of experience teaching students how to turn their technological ideas into a business venture and develop their entrepreneurial skills. The text is separated into three parts providing a roadmap towards successful business: - Part I focusses on how to create your venture, turning technology into businesses and how to link together entrepreneurship and innovation - Part II shows you how to grow your venture and make it profitable, looking at the early development of academic spin-outs and how to adapt your technology to the customers' needs. - Part III takes you through the day-to-day running on your business; whether to adopt a contingency or contextual approach, how to develop new products and services and alternative options for growth. With a wide range of practical steps, lists of things to consider and guidelines on how to turn your technology based ideas into a successful business, this text will be essential for all non-business students who need to understand entrepreneurship, management and innovation. It will also prove a useful introduction to all Masters-level students taking these subjects in business schools'--
Includes bibliographical references and index.
Keywords: Technological innovations -- Economic aspects; High technology industries -- Management; Entrepreneurship; Intellectual property; New business enterprises -- Management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management